Physical Properties of an Ionic Liquid Composed of Two Water-Soluble Vitamins and Enhanced Skin Permeation of Both Vitamins - Kenji Sugibayashi; Yuya Yoshida; Ryuichiro Suzuki; Kota Yoshizawa; Kenji Mori; Shoko Itakura; Kozo Takayama; Hiroaki Todo (MDPI AG, 2020)
A highly viscous substance was prepared by evaporating an ethanol solution containing two hydrophilic vitamins; vitamin C, and vitamin B6. The viscous substance and physical mixture of the two vitamins were tested using a differential scanning calorimeter and an X-ray diffractometer. The highly viscous substance was found to be a liquid crystal (LC) made of these two hydrophilic vitamins. Determination by proton nuclear magnetic resonance measurement suggested that intramolecular hydrogen bonding in vitamin B6 was eliminated by the LC formation. This LC compound showed high solubility in 1,3-butanediol (almost 87%). Much higher skin permeation of both vitamin C and B6 was also observed from the LC compound than that from the physical mixture. The present LC compound containing vitamin C and vitamin B6 may be useful for pharmaceutical and cosmeceutical applications.